Beckman Type CE Electroencephalograph, rear interior view - Beckman Instruments Photographic Services Section (1968)
Electroencephalographs are used to monitor and record electrical activity of the brain.
Keywords: Medical electronics--Equipment and supplies; Scientific apparatus and instruments; Electroencephalography; Beckman Instruments, Inc.